GAMBARAN IMPLEMENTASI REGULASI PENGELOLAAN LIMBAH NON MEDIS DAPUR GIZI DI RUMAH SAKIT - Ristiana; Noor, Ahmad Yani; siswatibudi , Harpeni; Janis Rupita, Aglita (Jurnal Permata Indonesia, 2025)
Hospital activities inevitably produce a considerable amount of waste, both medical and non-medical. One of the most common types of non-medical waste generated by hospitals is waste from the nutrition kitchen, which, if not properly managed, has the potential to become a medium for disease transmission. According to Minister of Health Regulation No. 7 of 2019, although classified as non-medical waste, its management still requires several mandatory stages. This study uses a descriptive qualitative method and was conducted in the nutrition kitchen of Arvita Bunda Specialized Mother and Child Hospital (RSKIA Arvita Bunda). The hospital has its own nutrition kitchen, and the waste management process is handled by a third party. In the management of non-medical waste from the nutrition kitchen, there is already a Standard Operating Procedure (SOP) in place as a reference. Supporting facilities and infrastructure for waste management are also available. However, there is still a mix of organic and inorganic waste. Temporary storage at the Temporary Disposal Site (TPS) is limited to a maximum of 2 days, but there are still piles of waste that exceed this time limit. Waste transport from the nutrition kitchen to the TPS does not yet use special trolleys, and the waste bins at the TPS are still inadequate. Final disposal of non-medical waste from the nutrition kitchen is carried out in cooperation with a third party. In general, although there are still some shortcomings in implementation, the non-medical waste management of the nutrition kitchen has met the requirements in accordance with Minister of Health Regulation No. 7 of 2019.